La suspensión condicional de lapPena en los delitos menores de 5 años y suiIncidencia en los procedimientos especiales - Moreira Muñoz, Marcia Concepción (2015)
The present thesis, the theme: “The suspension Conditional Sentence for crimes of five years and its impact on the special procedures.”, Consists of six chapters in which a synthesis of the subject under investigation unfolds. In the introduction , a conceptualization on the conditional suspension of sentence, in the exercise of criminal action, problematization is made, the reality of the Conditional Waiver of Penalty focuses avoid enforcement of compliance with the minimum penalty is notes the general and specific objectives, assumptions, independent and dependent variables and resources are detailed . In the theoretical framework, which consists of background research, rationale: Doctrine, Jurisprudence, Law and Comparative Law development is based on the conditional suspended sentence for offenses punishable by imprisonment up to five years? In the methodology , methods used to citizens are determined , the techniques used in the field , the implementation of surveys Santo Domingo de ECUADOR , lawyers and interviews with such results tabulation was performed , analysis and data processing , reporting of research and testing of the hypothesis was developed , conclusions and recommendations formulated . The proposed legal reform to art. 630 Professional Code highlighting the importance of proper legal form for conditional suspension of sentence.